Graphite/SiC junctions and their electrical characteristics. Issue 9 (29th May 2017) - Yatskiv, Roman; Grym, Jan
Abstract : Current–voltage characteristics of rectifying graphite/SiC junctions are investigated in a wide temperature range. The main parameters of the diodes, the ideality factor, and the Schottky barrier height show strong temperature dependence. Such behavior is interpreted on the basis of standard thermionic emission theory assuming Gaussian distribution of the barrier heights due to inhomogeneity at the graphite/SiC interface.